The Impact of Inpatient Room Tariff Structures on Hospital Revenue: Evidence from a Public Hospital in Indonesia - Rahayu Japar; Ambo Uleng (Liquidity Jurnal Ilmu Manajemen dan Bisnis, 2026)
Public hospitals in developing countries face increasing pressure to achieve financial sustainability while maintaining equitable access to care. This study aims to analyze the effect of inpatient room tariff calculation on hospital revenue performance at Haji Hospital Makassar, focusing on how pricing structures influence utilization patterns and income generation. This research employs a descriptive quantitative case study design using retrospective hospital data from 2011 to 2014. Data include inpatient room tariffs, utilization by room class, estimated costs, operational expenditures, and total hospital revenue. The analysis examines the relationship between tariff structures and revenue through aggregation and comparison of inpatient service data. The results show that inpatient services constitute the dominant source of hospital revenue, with room-based income contributing the majority share of total earnings. Despite a fixed tariff system, revenue trends varied due to changes in room utilization across different classes. Lower-priced rooms, particularly Class III, demonstrated the highest and most consistent growth in demand, ultimately becoming the largest contributor to inpatient revenue. In contrast, higher-priced rooms exhibited more volatile utilization patterns. These findings indicate that hospital revenue is influenced more by occupancy levels and demand distribution than by tariff magnitude alone. The discussion highlights that pricing strategies align with economic demand theory, where affordability drives utilization, and emphasizes the importance of balancing cost recovery with equitable access. In conclusion, inpatient room tariff structures significantly influence hospital revenue through their impact on utilization patterns. Effective pricing policies should integrate cost-based calculation, capacity management, and equity considerations to ensure sustainable and inclusive hospital financing.